Opinion: Understanding the impacts of agriculture and food systems on atmospheric chemistry is instrumental to achieving multiple Sustainable Development Goals - A. P. K. Tai; A. P. K. Tai; A. P. K. Tai; L. Luo; B. Luo (Atmospheric Chemistry and Physics)
Agriculture and food systems play important roles in shaping atmospheric chemistry and air quality, most dominantly via the release of reactive nitrogen (Nr) compounds but also via agricultural burning, energy use, and cropland and pastureland expansion. In this opinion article, we first succinctly review our current understanding of agricultural and food-system emissions of Nr and other atmospherically relevant compounds; their fates and impacts on air quality, human health, and terrestrial ecosystems; and how such emissions can be potentially mitigated through better cropland management, livestock management, and whole-food-system transformation. In doing so, we highlight important knowledge gaps that warrant more extensive research and argue that we scientists need to provide a more detailed, process-based understanding of the impacts of agriculture and food systems on atmospheric chemistry, including both chemical composition and processes, especially as the importance of emissions from other fossil-fuel-intensive sectors is fading in the face of regulatory measures worldwide. Such knowledge is necessary to guide food-system transformation in technologically feasible, economically viable, socially inclusive, and environmentally responsible ways and is essential to help society achieve multiple Sustainable Development Goals (SDGs), especially to ensure food security for people, protect human and ecosystem health, improve farmers' livelihoods, and ultimately help communities achieve socioeconomic and environmental sustainability.